Comunicación asertiva por whatsapp en docentes de las instituciones educativas públicas del nivel inicial, Caballo Cocha 2021 - Panduro Catashunga, Jarif Esther (2023)
The study focuses on assertive communication through WhatsApp, for this purpose the main objective was established to describe the level of assertive communication through WhatsApp in teachers of the initial level public Educational Institutions of Caballo Cocha in 2021. According to the objective was worked with the type of descriptive investigation, and as a design, the cross-sectional, field, and univariate design was used. A duly validated questionnaire was applied to the study population, which at the same time was the sample, using the data collection technique called survey. The results show that the level of assertive communication by WhatsApp of the 61 (100.0%) of the teachers of the initial level public educational institutions is low in 4.9% (n=3), while it is medium in 27.9% (n=17) and it is of a high level in 67.2% (n=41) who are the majority.